Pengembangan Kursi Kerja Ergonomis di UKM Tenun Ikat Medali Mas - Ary Permatadeny Nevita (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2019)
The role of humans as a source of labor in SME weaving is still very dominant in the production process, especially when the production process of converting yarn into fabric with non-machine looms. Sitting position during the process of weaving activities that lasts a long time with 8 hours per day, causes the sitting position to be less comfortable and cause complaints of pain in the back or spine. The purpose of this study is to produce an ergonomic work chair design with an anthropometric approach to improve comfort, reduce fatigue and other health effects caused by sitting positions that are less comfortable than the previous work chair, by focusing the work chair design on human body size. The results of this study are the development of weaving work chairs can be achieved by the addition of the backrest and cushion on the seat cushion of the chair as well as the addition of high-low chair settings according to anthropometry of workers compared to pre-existing weaving work chairs. Anthropometric measurements using the 5th and 95th percentiles obtained the dimensions of the work chair dimensions: 1) The height of the chair from the floor 95 cm, 2) The height of the seat cushion from the floor 52 cm, 3) The width of the seat base 39 cm, 4) The width of the backrest 35 cm, 5) Back length 31 cm, 6) Back height 49 cm. Peranan manusia sebagai sumber tenaga kerja pada UKM tenun ikat masih sangat dominan dalam proses produksinya terutama saat kegiatan proses produksi pengubah benang menjadi kain dengan alat tenun bukan mesin (ATBM). Posisi duduk pada saat proses pelaksaan kegiatan menenun yang secara terus menerus dengan waktu 8 jam per hari, menyebabkan posisi duduk menjadi kurang nyaman dan mengakibatkan   keluhan sakit terhadap punggung ataupun tulang belakang. Tujuan dari penelitian ini adalah menghasilkan rancangan kursi kerja yang ergonomi dengan pendekatan antropometri untuk meningkatkan kenyamanan, mengurangi kelelahan dan dampak-dampak negatif yang disebabkan akibat posisi duduk yang kurang nyaman dari kursi kerja sebelumnya, dengan memfokuskan rancangan kursi kerja pada ukuran tubuh manusia. Hasil dari penelitian ini adalah pengembangan kursi kerja tenun  dapat dicapai dengan penambahan sandaran serta bantalan pada alas tempat duduk pada kursi serta penambahan pada pengaturan tinggi rendah kursi sesuai dengan anthropometri pekerja dibandingkan dengan kursi kerja tenun yang sudah ada sebelumnya. Pengukuran secara anthropometri menggunakan persentil ke-5 dan ke-95 maka diperoleh rancangan dimensi kursi kerja: 1) Tinggi kursi dari lantai 95 cm, 2) Tinggi alas duduk dari lantai 52 cm, 3) Lebar alas kursi 39 cm, 4) Lebar sandaran 35 cm, 5) Panjang sandaran 31 cm, 6) Tinggi sandaran 49 cm.